Thermodynamic feasibility analysis of distributed chemical looping ammonia synthesis - Burrows, Laron; Gao, Pu-Xian; Bollas, George M. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
•Intensified ammonia synthesis is feasible through chemical looping.•Framework systematically evaluates chemical looping ammonia synthesis process options.•Results are ranked against performance metrics of energy intensity, efficiency, and cost.•Ca, Sr, Mn and Mo are shown most favorable for indirect ammonia synthesis. Stranded Natural Gas (SNG) flaring has increased over the last decade resulting in additional Green House Gas (GHG) emissions and underutilization of our finite fossil fuel resources. However, utilization of SNG is difficult due to its low volume, inconsistent composition, and intermittent flow. In this paper, intensified Chemical looping for Ammonia Synthesis (CLAS) is explored as a process suitable for remote deployment at SNG sites. CLAS mediate ammonia synthesis by using compounds that carry nitrogen and hydrogen in stepwise reactions, allowing ammonia synthesis under milder conditions and smaller, more flexible processes. The challenge in CLAS is to find a feasible combination of materials and process conditions that yield ammonia at economically acceptable rates. We propose a framework that systematically evaluates CLAS to determine their suitability for SNG deployment. CLAS reaction schemes are reviewed and organized based on the mediating compounds used to synthesize ammonia. Different compounds are evaluated for each CLAS in search of a thermodynamically spontaneous pair. Spontaneous CLAS flowsheets are, then, optimized to maximize ammonia output at equilibrium. The results are ranked against performance metrics of energy intensity, efficiency, and cost. Chemical loops with Ca3N2/CaH2, SrH2/Sr3N2, MnO2/Mn5N2 and MoO2/Mo2N are found to have favorable performance, along with literature-reported evidence and are recommended for further evaluation toward a distributed ammonia synthesis solution.